Постать Грегора Менделя: міфи і реалії. До 150-річчя оприлюднення Грегором Менделем результатів «Дослідів над рослинними гібридами» - Опалко, А.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. In order to know the personality of Gregor Mendel as one of the most outstanding fi gures of the XІXth century, whose efforts have laid the foundations of a new science of life — genetics, we had to fi nd out the sources of his formation and development. Methods. We’ve used the biographic method of studying an individual way, life experience and the scientifi c publications so that to make our investigation. Results. The meaning of some objective and subjective factors which braked Mendelizm recognition, so as the removal of biological sciences from mathematics and imperfection of experiment methodology and excitement discussion developed in the biological science, concerning the book by Charles Darwin «On the origin of species by means of natural selection, or the preservation of favoured races in the struggle for life» which had been published six years earlier; was fi nd out owing to the retrospective analysis of Mendelism history as the basis of classical genetics. The efforts of an ancient authors so as the attempts of philosophers of the Age of the Enlightenment which tried to discuss the facilities before Gregor Mendel were observed. The reasons of Gregor Mendel and Mendelism mythologizing were discussed while the odious myths were rebutted. The individual aspects of Lysenkoism bad infl uence onto the biologiacal science in the USSR and Ukraine were revealed. Conclusions. An outstanding fi gure of Gregor Mendel have been obtained the greatest signifi cance and attraction; he was really great scientist — example for imitation for the present and coming generation of scientists. His example became the more meaningful for the scientists of XІXth century who have been developing the genetics in the conditions of powerful synergistic researches so as the new ideas, theories and images. Keywords: Charles Darwin, Green revolution, history of genetics, life sciences, Lysenkoism, Mendelism, synergistic research.